AVS Generic Audio Coding - Hu Ruimin; Chen Shuixian; Ai Haojun; Xiong Naixue (Sixth International Conference on Parallel and Distributed Computing Applications and Technologies (PDCAT'05), 2005)
AVS Audio Coding Standard is the first standard for Hi-Fi audio in China. The framework of AVS Audio was introduced. Many key technologies are described in details, including long/short window switch decision based on energy and unpredictability, integer MDCT for lossless time-frequency transform, square polar stereo coding, and context-dependent bitplane coding for scalable entropy coding. The informal subject test result is given between AVS audio codec and several dominating audio codecs. It is shown that AVS audio codec is enough for Hi-Fi audio applications.